PENGEMBANGAN MODUL PENCEGAHAN STUNTING UNTUK CALON PENGANTIN DI KUA KOTO TANGAH - Irba Khesa; John Amos; Nindy Audia Nadira; Erick Zicof; Evi Maria Lestari Silaban (Poltekkes Kemenkes Bengkulu, 2025)
Stunting is a chronic nutritional problem that hampers children’s growth and development. According to the 2022 Indonesia Nutrition Status Survey (SSGI), the national stunting prevalence was 21.6%. In 2023, Koto Tangah recorded the highest stunting rate in Padang at 13.83%. Although premarital education has been provided through BP4 (Badan, Penasihat, Pembinaan, dan Pelestarian Perkawinan) activities at the KUA, stunting prevention has not yet become a primary topic.This study employed a qualitative method with a case study approach.Data were collected through in depth interviews and observation. The data were analyzed using data reduction, data presentation, and conclusion drawing. The study involved 15 informants, 9 prospective couple as primary informants, 1 head of KUA as a key informant, and 4 supporting informants consisting of the program manager for marriage guidance, nutrition officer, design expert, and language expert.The findings indicate that prospective couple have limited knowledge about stunting. Most of them are unaware of the importance of stunting prevention starting before pregnancy due to minimal exposure to relevant information. Existing preventive efforts are still limited to counseling for those with anemia. To address this need, an analysis was conducted using the P-Process approach to develop the SEHATI module as an educational medium suited to the target audience.The SEHATI module has been tested on informants and is considered appropriate for the target characteristics. It is recommended to integrate this module into BP4 counseling materials and disseminate it through KUA and health facilities as a self-education tool for prospective couple.